A CRITIQUE OF EMBODIMENT (The Strategic Review for Southern Africa, 2020)
Embodiment is often taken for granted as beneficial to our wellbeing, learning andhealing. Embodied processes are core to various therapies and pedagogies. Current debates on decolonising knowledge, education, museums, universities andcurriculums are suggesting that more art courses, more creative practices andembodied methodologies will provide solutions to the resilient crisis of transformation, representation, separateness and woundedness effected by centuries of colonial and apartheid violence. In the context of genocide and violence, however, an attempt to transform and heal from its trauma, embodiment should be applied with caution. Arts and other embodied approaches may be dislocating and possibly re-traumatising if applied from a philosophical, theoretical, psychological and academic logic that emphasises the notion of separation which locates the body to the margins, and isolates individuals and communities from themselves, each otherand the world. In light of the metaphors going back home and the journey to healing, emerging from experiences and processes of survival and healing, this article proposes REmbodiment (reembodiment). Re-embodied are here understood as practices that take their source and feed modes of being and praxis that are more circular, opening, re-membering (bringing together, repairing), interconnecting, multidimensional.It occurred to me then that if one could make a people lose touch withtheir capacity to create, lose sight of their will and their power to makeart, then the work of subjugation, of colonization, is complete. Suchwork can be undone only by acts of concrete reclamation(Hooks 1995: xv)